Hard time at Tehachapi: California's first women's prison - Cairns, Kathleen A. (University of New Mexico Press, 2009)
San Quentin blues : criminals, clubwomen, and the campaign for a female reformatory -- Hard-nosed politics : the battle for Tehachapi -- Murderers, thieves, and con artists -- Writing their lives : the Clarion and the California Institution for Women -- A woman in charge -- Tehachapi : on shaky ground -- After Tehachapi